Doing Business in 2005 : Removing Obstacles to Growth - World Bank (Doing Business, 2004)
Doing Business in 2005: Removing Obstacles to Growth is the second in a series of annual reports investigating the scope and manner of regulations that enhance business activity and those that constrain it. New quantitative indicators on business regulations and their enforcement can be compared across 145 countries-from Albania to Zimbabwe-and over time. The previous report, Doing Business in 2004: Understanding Regulation, presented indicators in five main topics: starting a business, hiring and firing workers, enforcing contracts, getting credit and closing a business. Doing Business in 2005 updates these measures and adds another two sets: registering property and protecting investors. The indicators are used to analyze economic and social outcomes, such as productivity, investment, informality, corruption, unemployment, and poverty, and identify what reforms have worked, where and why. In Doing Business in 2005, you will also find answers to such questions as: Which are the Top 10 reformer countries since last year? Which are the Top 20 economies for doing business? As well as which countries implemented more harmful regulations? Doing Business is a comprehensive resource that no investor, policymaker, or economic advisor should be without